An Integrated approach for knowing the Land Resource Inventories of Palarnau, Distt. Bihar - Ali, Sharafat; Nayan, Kamal; Gawande, S.P. (Journal of Soil and Water Conservation, 2022)
Soil survey adopting sampling technique was conducted in Palaniau district, Bihar for generating basic soil and land resources data for development and planning involving land and water management. The data collected in the survey were interpreted for different soil and land qualities, potentialities and capabilities. The survey revealed that existing land use in the area comprises 40.4% under rainfed crop lands, 2.4% under irrigated crop lands and 4.9% under grass cum pasture and culturable waste lands. Nearly 68 % area which consisted of 29.8%, 10.0%, 13.5%, 36.9% and 3.8% under 11; III, I i; VI and VII land capability classes respectively needs soil conservation and water manage- ment planning. The specific problems and proposed soil and water conservation measures are discussed in the paper